J
You get the same answer, you just start with (x + 3) in the second equation...
That moment when you realize you're dumb and the correct answer is F
When you see the symbol "△", this denotes a triangle. Now combine the symbol with the letters FGH, this becomes △FGH, meaning a triangle FGH, with F, G, and H as the three points.
Now, the symbol "∠" means angle and "m∠" means the measure of an angle. So m∠F means the angle at the point F, m∠G means the angle at the point G, and m∠H means the angle at the point H. (I'll attach a diagram of this triangle).
Now we have to determine m∠H, which is the angle at point H. To do that, we have to find the value of
. To do that, we have to use one of the laws of a triangle, which is:
The sum of angles in a triangle = 180°. This means when we add all the angles in a triangle, it sums up to 180°. Let's do that.
![\angle F + \angle G + \angle H = 180\textdegree \\\angle F = (5x - 6)\textdegree, \angle G = (3x + 16)\textdegree, \angle H = (x + 8)\textdegree \\(5x - 6) + (3x + 16) + (x + 8) = 180\\5x + 3x + x - 6 + 16 + 8 = 180\\9x + 18 = 180\\9x = 180 - 18\\9x = 162\\x = 18\textdegree](https://tex.z-dn.net/?f=%5Cangle%20F%20%2B%20%5Cangle%20G%20%2B%20%5Cangle%20H%20%3D%20180%5Ctextdegree%20%5C%5C%5Cangle%20F%20%3D%20%285x%20-%206%29%5Ctextdegree%2C%20%5Cangle%20G%20%3D%20%283x%20%2B%2016%29%5Ctextdegree%2C%20%5Cangle%20H%20%3D%20%28x%20%2B%208%29%5Ctextdegree%20%5C%5C%285x%20-%206%29%20%2B%20%283x%20%2B%2016%29%20%2B%20%28x%20%2B%208%29%20%3D%20180%5C%5C5x%20%2B%203x%20%2B%20x%20-%206%20%2B%2016%20%2B%208%20%3D%20180%5C%5C9x%20%2B%2018%20%3D%20180%5C%5C9x%20%3D%20180%20-%2018%5C%5C9x%20%3D%20162%5C%5Cx%20%3D%2018%5Ctextdegree)
Now that we have found the value of x as 18°, we can substitute its value to determine the angle H.
![m\angle H = (x + 8), x = 18\\m\angle H = 18 + 8\\m\angle H = 26\textdegree](https://tex.z-dn.net/?f=m%5Cangle%20H%20%3D%20%28x%20%2B%208%29%2C%20x%20%3D%2018%5C%5Cm%5Cangle%20H%20%3D%2018%20%2B%208%5C%5Cm%5Cangle%20H%20%3D%2026%5Ctextdegree)
I hope you understand the explanation.
Answer:
1) √10 units
A=(-1, 0) let us assume (x1, y1)
B=(2, 1) let us assume (x2,y2)
distance= √(x2-x1)^2 + (y2-y1)^2
=√(2+1)^2 + ( 1-0)^2
=√3^2 + 1^2
= √10 units
Answer: B.
Step-by-step explanation:
See attached. We examine the equation and decide which situation, or problem, models it correctly.